EVALUASI KINERJA STRUKTUR BANGUNAN BETON BERTULANG DI TANAH KHUSUS BERDASARKAN ANALISIS PUSHOVER: EVALUASI KINERJA STRUKTUR BANGUNAN BETON BERTULANG DI TANAH KHUSUS BERDASARKAN ANALISIS PUSHOVER - halima tusadiyah (LPPM Universitas Abdurrab, 2021)
Site class F is a profile of soil layers that are prone to failure or collapse due to earthquake loads such as liquefaction, highly sensitive clays, weak cemented soils, and highly organic clays that require specific geotechnical investigations and site-specific response analysis. One of the factors that influence design of earthquake-resistant the building structures is condition of the soil layer and and analysis structure. This study aims to evaluate the performance of reinforced concrete structures on site class F using the pushover analysis method. Pushover analysis is a non-linear static method in which a structure is subjected to gravitational loading and a lateral load pattern controlled by monotonic displacement which continues to increase through elastic and inelastic behavior until final conditions are reached. The results showed that the performance level of the pushover analysis structure based on the ATC-40 structure is included in the Damage Control category level.